Answer:
3) (2,-9)
4) (0,-5)
5) (1,-8)
Step-by-step explanation:
3)
The vertex will occur between you x-intercepts.
You already found that happens at x=2.
To find the corresponding y-coordinate, replace x in
f(x)=(x+1)(x-5) with 2:
f(2)=(2+1)(2-5)
f(2)=(3)(-3)
f(2)=-9
So the vertex is (2,-9).
4)
The y-intercept is when x=0.
So in f(x)=(x+1)(x-5) replace x with 0:
f(0)=(0+1)(0-5)
f(0)=(1)(-5)
f(0)=-5
So the y-intercept is (0,-5).
5)
To find another point just plug in anything besides any x already used.
We preferably want to use a value of x that will keep us on their grid however far up,down,left, or right their grid goes out. So I'm going to choose something close to the vertex which is at x=2. Let's go with x=1.
So replace x in f(x)=(x+1)(x-5) with x=1:
f(1)=(1+1)(1-5)
f(1)=(2)(-4)
f(1)=-8
So another point to graph is (1,-8).
Answer:
A
Step-by-step explanation:
(x+2)(x+2)
= x^2+2x+2x+4
=x^2+4x+4
The answer is :
![4x - 3 < 32 \\ 4 x < 32 + 3 \\ 4 x < 35 \\ x < \frac{35}{4} \\](https://tex.z-dn.net/?f=4x%20-%203%20%3C%2032%20%5C%5C%204%20x%20%3C%2032%20%2B%203%20%5C%5C%204%20x%20%3C%2035%20%5C%5C%20x%20%3C%20%20%5Cfrac%7B35%7D%7B4%7D%20%20%5C%5C%20)
![x < 8.75](https://tex.z-dn.net/?f=x%20%3C%208.75)
and the only number among the choices that is less than 8.75 is -6
hope it's true
Answer:
11/15 = 0.733333
But the terminating decimal is 0.73
Step-by-step explanation:
Answer:
<h2>The easiest to solve for is x in the first equation</h2>
Step-by-step explanation:
Given the system of equation, x + 4 y = 14. and 3 x + 2 y = 12, to solve for x, we can use the elimination method of solving simultaneous equation. We need to get y first.
x + 4 y = 14............ 1 * 3
3 x + 2 y = 12 ............ 2 * 1
Lets eliminate x first. Multiply equation 1 by 3 and subtract from equation 2.
3x + 12 y = 42.
3 x + 2 y = 12
Taking the diffrence;
12-2y =42 - 12
10y = 30
y = 3
From equation 1, x = 14-4y
x = 14-4(3)
x = 14-12
x = 2
It can be seen that the easiest way to get the value of x is by using the first equation and we are able to do the substitute easily <u>because the variable x has no coefficient in equation 1 compare to equation 2 </u>as such it will be easier to make the substitute for x in the first equation.